Improved bounds of Mitrinović–Adamović-type inequalities by using two-parameter functions - Guiping Qian; Xiao-Diao Chen (Journal of Inequalities and Applications, 2023)
Abstract This paper provides improved bounds of inequalities of Mitrinović–Adamović type by using two-parameter functions. It achieves a much better approximation effect than those bounds of prevailing methods. A new method based on the Páde interpolation is used to prove the new bounds, which can also be applied for proving the results of prevailing methods and their much more generalized results.